PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SDN 21 BANDAR BUAT KOTA PADANG - Amelia, Citra; Zuryanty; Yanti Fitria; Ummiatul Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning Science and Social Studies (IPAS) in the Merdeka Curriculum requires active student participation as well as critical thinking and problem-solving skills; however, in practice, learning outcomes in IPAS at the elementary school level remain relatively low and instruction tends to be teacher-centered. This study aims to improve students’ learning outcomes in IPAS through the implementation of the Problem Based Learning (PBL) model in Grade IV of SDN 21 Bandar Buat, Padang City. This research employed a mixed-methods approach (qualitative and quantitative) using Classroom Action Research conducted in two cycles. The research subjects consisted of 27 students. Data were collected through observation, tests, and non-test techniques, and analyzed descriptively. The results indicate that the implementation of the PBL model effectively improved students’ learning outcomes, as shown by an increase in the average score from 72.96 with a mastery level of 40.7% in Cycle I to ≥85 with classical mastery of ≥85% in Cycle II. Therefore, the Problem Based Learning model is effective in improving IPAS learning outcomes and supporting the implementation of the Merdeka Curriculum in elementary schools.